2015
DOI: 10.1371/journal.pone.0125306
|View full text |Cite|
|
Sign up to set email alerts
|

Misunderstanding of Front-Of-Package Nutrition Information on US Food Products

Abstract: Front-of-package nutrition symbols (FOPs) are presumably readily noticeable and require minimal prior nutrition knowledge to use. Although there is evidence to support this notion, few studies have focused on Facts Up Front type symbols which are used in the US. Participants with varying levels of prior knowledge were asked to view two products and decide which was more healthful. FOPs on packages were manipulated so that one product was more healthful, allowing us to assess accuracy. Attention to nutrition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…This result is in line with several studies that show that consumers usually find it difficult to assess nutritional information in the form of numbers and percentages (44)(45)(46) . According to Soederberg Miller et al (47) , when consumers are not provided with reference information, small differences between products in the content of one or two nutrients may drive the decision, without consideration of other important nutrients. For this reason, interpretational aids and reference information improve consumer ability to identify the most healthful alternative among a set of products (17,19,33,48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with several studies that show that consumers usually find it difficult to assess nutritional information in the form of numbers and percentages (44)(45)(46) . According to Soederberg Miller et al (47) , when consumers are not provided with reference information, small differences between products in the content of one or two nutrients may drive the decision, without consideration of other important nutrients. For this reason, interpretational aids and reference information improve consumer ability to identify the most healthful alternative among a set of products (17,19,33,48,49) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to select the more healthful choice, individuals must be capable of distinguishing between meaningful nutrient differences across the food choices and minor differences, which can be challenging even when relying on simplified (ie, FOP) labels. 25 A secondary goal was to replicate past findings on the effects of training on labelreading accuracy, perceptions of empowerment, and usability of the Web-based tool.…”
Section: Introductionmentioning
confidence: 98%
“…There is also some evidence, suggesting that even these abbreviated forms of information may have no impact on purchasing intentions, cause confusion among consumers, or detract from other important information. 22,[25][26][27] Another approach to improving capability involves teaching individuals how to read nutrition facts labels. This approach also capitalizes on opportunityin the form of existing widespread, reliable, and uniform informationand potentially increases motivation to the use nutrition information on labels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the influence of consumer understanding and demographic characteristics on use of the NFt and other nutrition marketing on food labels (e.g. health claims, nutrient content claims and front-of-pack labels) [5][6][7][8][9][10][11]. These studies show that although consumers can make simple comparisons between similar products, many have difficulties understanding how to evaluate the information presented on the package with respect to healthfulness [8,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%